(untitled) (Bangladesh Journal of Zoology, 2016)
The habitat analysis of stork-billed kingfisher (Pelargopsis capensis Linnaeus, 1766) and pied kingfisher (Ceryle rudis Linnaeus, 1758) was done at the Chittagong University Campus, Chittagong, Bangladesh during January 2011 to December 2013. The both kingfisher species used five types of habitat (pond, lake, stream, agricultural land/channel and tree), of which trees were used maximum (43.23%) and agricultural lands/channels were minimum (3.76%) by stork-billed kingfisher; whereas pied kingfisher spent the highest time (40.66%) in the streams and the lowest (11.67%) in the agricultural lands/channels. Four types of perching places (fence, wire, bamboo and tree) were used by both kingfisher species, of which trees were used maximum (68.89%) and wires minimum (2.78%) by stork-billed kingfisher; while pied kingfisher spent the highest (53.43%) time on fences and the lowest (4.78%) on wires. Bangladesh J. Zool. 43(2): 251-268, 2015